PENGARUH MOTIVASI, KOMPETENSI, INDEPENDENSI, MORAL REASONING, TIME BUDGET PRESSURE DAN SKEPTISISME AUDITOR TERHADAP KUALITAS AUDIT (Studi Kasus Pada Pemeriksa BPK RI Perwakilan Provinsi Jawa Tengah) - Feri Ardiansyah, 11.05.52.0030; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
The purpose of this research is to analyse the influence of motivation, competency, independency, moral reasoning, time budget pressure and auditorâs scepticism to audit quality on the BPK RI Representative of Province in Central of Javaâs auditors. The population of this research are all auditor which have followed Education and Training of Functional Posision of Auditor (JFP) and have minimum 2 years job experience as auditor. Sampling was conducted using a purposive sampling method and number of samples of 97 respondents. The data analysis technique used in this research is the technique of multiple regression analysis. The result showed that the competency, moral reasoning andÂ  auditorâs skepticism have a positive and significant impact on audit quality. while the motivation, independency and time budget pressureÂ  donât have a significant impact on audit quality.Keywords: Motivation, Competency, Independency, Moral Reasoning, Time Budget Pressure, Auditorâs Scepticism, Audit Quality